Household education spending in Latin America and the Caribbean: Evidence from income and expenditure surveys - Santiago Acerenza; Néstor Gandelman (Inter-American Development Bank (IDB), 2017)
This paper characterizes household spending in education using microdata from income and expenditure surveys for 12 Latin American and Caribbean countries and the United States. Bahamas, Chile and Mexico have the highest household spending in education while Bolivia, Brazil and Paraguay have the lowest. Tertiary education is the most important form of spending, and most educational spending is performed for individuals 18-23 years old. More educated and richer household heads spend more in the education of household members. Households with both parents present and those with a female main income provider spend more than their counterparts. Urban households also spend more than rural households. On average, education in Latin America and the Caribbean is a luxury good, while it may be a necessity in the United States. No gender bias is found in primary education, but households invest more in females of secondary age and up than same-age males.
Keywords: E21; I2; D12; 330; Education; Income and expenditure surveys; Engel equations; Latin America